Changes to Chevron BD's approach to learning and development: a comparative analysis of pre-pandemic vs. post-pandemic approaches - Khan, MD Raiyan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.